Cognitive Screening in Brain Tumors: Short but Sensitive Enough? - Robinson, Gail A.; Biggs, Vivien; Walker, David G. (Frontiers in Oncology, 2015)
Cognitive deficits in brain tumours are generally thought to be relatively mild and nonspecific, although recent evidence challenges this notion. One possibility is that cognitive screening tools are being used to assess cognitive functions but their sensitivity to detect cognitive impairment may be limited. For improved sensitivity to recognise mild and/or focal cognitive deficits in brain tumours, neuropsychological evaluation tailored to detect specific impairments has been thought crucial. This study investigates the sensitivity of a cognitive screening tool, the Montreal Cognitive Assessment (MoCA), compared to a brief but tailored cognitive assessment for identifying cognitive deficits in an unselected primary brain tumour sample (i.e., low/high grade gliomas, meningiomas). Performance is compared on broad measures of impairment: a) number of patients impaired on the global screening measure or in any cognitive domain; and b) number of cognitive domains impaired and specific analyses of MoCA-Intact and MoCA-Impaired patients on specific cognitive tests. The MoCA-Impaired group obtained lower naming and word fluency scores than the MoCA-Intact group, but otherwise performed comparably on cognitive tests. Overall, based on our results from patients with brain tumour, the MoCA has extremely poor sensitivity for detecting cognitive impairments and a brief but tailored cognitive assessment is necessary. These findings will be discussed in relation to broader issues for clinical management and planning, as well as specific considerations for neuropsychological assessment of brain tumour patients.